1
$\begingroup$

Evaluate the partial fraction decomposition of $\pi \tan(\pi z)$

$$2\pi \tan(\pi z)=\cot\left(\frac{\pi}{2}-\pi z\right)-\cot\left(\frac{\pi}{2}+\pi z\right)$$ $$=\frac{2}{1-2z}+\sum_{k=1}^\infty \frac{1-2z}{(\frac{1}{2}-z)^2-k^2}-\frac{2}{1+2z}-\sum_{k=1}^\infty \frac{1+2z}{(\frac{1}{2}-z)^2-k^2}$$ $$=\frac{8z}{1-4z^2}+\sum_{k=1}^\infty \frac{4-8z}{1-2z+4z^2-4k^2}-\sum_{k=1}^\infty \frac{4+8z}{1+2z+4z^2-4k^2}$$ I know that the result should be $$\pi \tan(\pi z)=\sum_{k=1}^\infty \frac{8z}{(2k+1)^2-4z^2}$$ but I dont know how to get there. Any suggestions?

$\endgroup$
  • $\begingroup$ You can get paretheses to adjust to the size of their content by using \left and \right. $\endgroup$ – joriki Jun 13 '16 at 19:39
4
$\begingroup$

Hint. If you know that, for $0<z<1/2$, $$ \pi \cot (\pi z)=\sum_{k=1}^\infty \left(\frac{1}{z-k}+\frac{1}{z+k-1}\right) $$ then by putting $z \to 1/2-z$ you get $$ \begin{align} \pi \cot (\pi (1/2-z))&=\pi \tan(\pi z) \\\\&=\sum_{k=1}^\infty \left(\frac{1}{1/2-z-k}+\frac{1}{1/2-z+k-1}\right) \\\\&=\sum_{k=1}^\infty\frac{8 z}{(2k-1)^2-4 z^2} \end{align} $$ as wanted.

$\endgroup$
  • $\begingroup$ I know that $\pi cot(\pi z)=\frac{1}{z} + \sum_{k=1}^\infty \frac{1}{z-n}+\frac{1}{z+n}$ $\endgroup$ – serge Jun 13 '16 at 20:13
  • 1
    $\begingroup$ @serge This is the same identiy as the first I wrote in my answer above, since by telescoping $\sum _{k=1}^{\infty } \left(-\frac{1}{z+k}+\frac{1}{z+k-1}\right)=\frac1z.$ $\endgroup$ – Olivier Oloa Jun 13 '16 at 20:38
1
$\begingroup$

You may exploit the fact that $\tan(z)=\frac{d}{dz}\log(\cos z)$ and: $$ \cos(z)=\prod_{n\geq 0}\left(1-\frac{4z^2}{(2n+1)^2\pi^2}\right)\tag{1}$$ (Weierstrass product) so: $$ \tan(z) = \sum_{n\geq 0}\frac{-8z}{4z^2-(2n+1)^2\pi^2}\tag{2}$$ and: $$\begin{eqnarray*}\pi\tan(\pi z) = \sum_{n\geq 0}\frac{-2z}{z^2-\left(\frac{2n+1}{2}\right)^2}&=&-\sum_{n\geq 0}\left(\frac{1}{z-\frac{2n+1}{2}}+\frac{1}{z+\frac{2n+1}{2}}\right)\\&=&\color{red}{\sum_{m\in\frac{1}{2}+\mathbb{Z}}\frac{-1}{z-m}}.\tag{3}\end{eqnarray*}$$

On the other hand, every singularity of $\pi\tan(\pi z)$ is a simple pole and lie in $\frac{1}{2}+\mathbb{Z}$,
and for every $m$ that belongs to such a set: $$ \text{Res}\left(\pi\tan(\pi z),z=m\right)=\lim_{z\to m}\frac{\pi\sin(\pi z)(z-m)}{\cos(\pi z)}\stackrel{DH}{=}\lim_{z\to m}\frac{\pi\sin(\pi z)}{-\pi \sin(\pi z)}=\color{red}{-1},\tag{4}$$ giving another proof of $(3)$.

$\endgroup$
  • $\begingroup$ This is a nice proof. $\endgroup$ – serge Jun 14 '16 at 6:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.